Foreign Direct Investment Led Growth Hypothesis and Economic Development in Nigeria - Ubong Edem Effiong; Nora Francis Inyang (RIRAI Publisher, 2021)
This study was an inquiry into the nexus of the foreign-direct investment (FDI) led growth hypothesis, and how it translates into the development of the Nigerian economy as of 1970 – 2018. The study utilized secondary data from the ‘World Development Indicators’ which were analysed using the Bounds test for cointegration and the ‘autoregressive distributed lag (ARDL) approach to divulge both the short-term cum the long-term influence of foreign direct investment net inflow on ‘economic development’ of Nigeria. The Bounds test was conducted after the unit root test revealed that the variables were stationary at mixed order of level and first difference. The outcome of the ARDL Bounds test supported confirmation of long-term association among the variables. The ARDL short-run error correction showed that 14.62% of the instability in the model was corrected yearly. In the short-term, it was discovered that FDI wielded a deleterious and substantial weight on ‘economic development of Nigeria. Meanwhile, the long-term estimates indicated that FDI influenced economic development positively, though not in a significant manner. The Granger causality test supported the fact that FDI causes ‘economic development’ in Nigeria. Given this potential of FDI exerting a positive effect on ‘economic development’, the paper recommended that bottlenecks inherent in FDI influxes in the country should be removed so as to reap the fullest benefits of such inflows in Nigeria.